As políticas públicas na área de gestão de pessoas da Universidade Federal do Tocantins: o aproveitamento coerente dos conhecimentos dos servidores técnico-administrativos com qualificação “stricto sensu” - Santos, Oldiley de Sousa (Universidade Federal do Tocantins, 2019)
This dissertation tries to understand what policies in the area of People Management are employed with respect to the use of the knowledge of the administrative technicians with master's and doctoral degrees at the Federal University of Tocantins. Facing that, the specific goals of this paper are to accomplish the mapping in the area of training in the strict sense of the technical-administrative servers of UFT; describe if the People Management of UFT performs any initiative to use the strict sense knowledge of the servers; If there are no initiatives to use the referred knowledge, to propose guidelines for a management policy that includes a better use of technical-administrative servers with a stricto sensu degree. As a general objective, it was aimed to understand which public policy in the area of People Management UFT employs for the coherent use of the knowledge of its technicaladministrative servants who have stricto sensu post-graduation. As a methodological course, an exploratory research was carried out, where definitions of Public Policies, Public Policy Management; People Management and its practices; Management by Competences; Knowledge Management; Qualification Policies for technicaladministrative servers of the UFT and Qualification at the stricto sensu level. After that, we proceeded to content analysis of document research of institutional initiatives in promoting stricto sensu qualification aimed at their technicaladministrative staff; mapping the stricto sensu formation areas; participant research in the central unit that manages the implementation of the career plan of the administrative-technicians and interview with the technical-administrative servers of the UFT with master's and doctoral degrees. It was found that the UFT implements many actions that promote the qualification in the strict sense level of its technical and administrative servers. However, there are no initiatives for the use of knowledge of these servers. Given that, it is needed a discussion about the creation of public policy actions in the area of personnel aimed at consistent utilization of knowledge of the administrative-technicians with stricto sensu post-graduation. This initiative should aim at the elaboration of a model of public policy in the area of People Management that will take into consideration the area of knowledge of the server.